Preparasi katalis MgO/C dari pirolisis polimer berbasis magnesium salisilat dan aplikasinya untuk reaksi transesterifikasi - Imam Prasetyo; Dwiana Ayu Kiranti Nur’aeni; Pandu Timur Bhaskara (Jurnal Rekayasa Proses, 2021)
The objective of the study is to produce carbon-based magnesium oxide (MgO) solid base catalyst by pyrolysis of phenolic resin and to examine the material effectiveness as a catalyst for transesterification reaction. The phenolic resins were prepared by polymerization process of phenol, derivative salicylic acid (magnesium salicylate), and formaldehyde aqueous solution under acidic condition using H2SO4 as catalyst. The molar ratio of magnesium salicylate:phenol:formaldehyde was 0.33:0.67:2.80. Carbon-based magnesium oxide solid base catalyst (MgO/C) was produced from phenolic resins via physical activation process using steam at 850°C. Material was characterized using N2-sorption analysis, X-ray diffraction (XRD) and scanning electron microscopy (SEM). Pyrolysis process for carbon formation resulted in 75% burn-off. The specific surface area of catalyst was 494 m2/g and the presence of MgO was confirmed by XRD diffraction pattern (2θ position of 36-43°, 61-63°, dan 74-78° according to JCPDS No.89-7746) and SEM image. Characteristic comparison of MgO/C with carbon produced from phenol formaldehyde resin (without magnesium salicylate) corroborate the finding that MgO/C was achieved. The catalyst was tested for transesterification reaction between palm oil and methanol. Conversion of 28.3% was achieved at temperature of 65 °C, reactant ratio of methanol: palm oil = 6:1 and reaction time of 2.5 hours. The activation energy of 6,444 cal/mol was obtained when evaluated in the range of 55-65 °C reaction temperature.